2022
DOI: 10.3390/ijms23179702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Photoperiod on Light-Dependent Photosynthetic Reactions in Cannabis

Abstract: Industrial hemp is a fast-growing, short-day plant, characterized by high biomass yields and low demands for cultivation. To manipulate growth, hemp is usually cultivated under prolonged photoperiods or continuous light that could cause photooxidative damage and adjustments of photosynthetic reactions. To determine the extent of changes in photosynthetic response caused by prolonged light exposure, we employed chlorophyll a fluorescence measurements accompanied with level of lipid peroxidation (TBARS) and FT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Thus, the electron-transport capacity of PSII is reduced [59]. These results are similar to earlier studies on grass [60], cannabis [24] and fresh-water plants [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the electron-transport capacity of PSII is reduced [59]. These results are similar to earlier studies on grass [60], cannabis [24] and fresh-water plants [27].…”
Section: Discussionsupporting
confidence: 90%
“…Study of the physiological mechanisms by which plants adapt to artificial light at night will help to select the species suitable for urban plantations and, consequently, to determine the success of urban plantations. Indeed, few previous studies were conducted in the natural environment, and most of the earlier findings on artificial light at night (ALAN) were mainly focused on plant ecosystem sustainability, while the studies showing the effects of ALAN on plant physiological processes were reported in very small numbers [24][25][26][27]. Trees growing under street-light conditions experience an extremely heterogeneous environment; therefore, the use of traditional analytical approaches in the early detection of stress would be expensive and time-consuming [28].…”
mentioning
confidence: 99%
“…The fully recovered φ R0 and δ R0 to the control values in white cabbage corroborated the increase in the electron flow rate at the PSI acceptor side (negative G band). Such results suggested the formation of functional adaptations as a response to drought in white cabbage [77,84,85].…”
Section: Changes In Jip-test Parameters After Drought and Recoverymentioning
confidence: 76%
“…A positive G band indicated a decrease in the PSII acceptors pool, accompanied by reduced electron transport and a subsequent reduction in the PSI reduction rate [75]. On the other hand, the negative G band seen in white cabbage was suggested to be a compensatory mechanism developed by plants exposed to inadequate and stressful conditions [37,77]. In such conditions, the number of available NADP + molecules increased, which, in turn, increased the activity of PSI [37,75].…”
Section: Changes In Ojip Transients After Drought and Recoverymentioning
confidence: 99%
“…adjust to changes in photoperiod. The adaptation strategy used by an organism to carry out photosynthesis depends on the type of light and the length of the photoperiod (Gajdošik et al, 2022). Short photoperiods can reduce the time available for photosynthesis, while long photoperiods provide more time for that process.…”
Section: Discussionmentioning
confidence: 99%